Synthesis of high purity silica from low cost water glass via sol-gel process and soxhlet extraction - Gu, Bongjun; Ko, Dongwook; Ahn, Seokhoon; Hyun, Dong Choon; Lee, Hyun-Kwuon; Kim, Jongbok (SPRINGER, 2017)
This study describes a strategy to economically synthesize silica with high purity. For economical synthesis, it is critical to choose proper synthetic process and raw material. Here, we have used economical sol-gel process and water glass with low cost to synthesize a silica powder, and adopted extraction process to enhance its purity. Specially, we have first examined where impurities are mainly located. Then we have considered how to enhance cleaning efficiency during extraction process for achievement of high purity. Scanning electron microscope and energy-dispersive X-ray spectroscopy analysis demonstrate that the impurities prefers to locate at the surface of silica aggregates, which indicates that large aggregates in size easily expose most of the impurities into the surface of silica whereas small sized aggregates can trap the impurities between them. Taken together with these results, we have formed large silica aggregates in size via controlling pH condition during the silica synthesis, followed by conducting Soxhlet extraction process for cleaning the impurities out. The use of this approach allows us to synthesize the silica with a purity of 99.95 wt%.
Keywords: PORE STRUCTURE; NANOCOMPOSITES; NANOPARTICLES; TEMPLATE; XEROGELS; SENSOR; PH